Toxicity and Dermatokinetic Analysis of Ibrutinib in Human Skin Models - Maria Victória Souto-Silva; Elizabete C. I. Bispo; Lucas F. F. Albuquerque; Stefhani Barcelos; Emãnuella M. Garcez; Luana S. Quilici; Florêncio Figueiredo Cavalcanti Neto; Eliza Carla Barroso Duarte; Jankerle N. Boeloni; Felipe Saldanha-Araujo; Guilherme M. Gelfuso; Juliana Lott Carvalho (MDPI AG, 2024)
Background/Objectives: Ibrutinib (IBR) is a tyrosine kinase inhibitor under investigation in preclinical and clinical settings as an alternative treatment for melanoma. Nevertheless, the limited oral bioavailability of IBR and the need for high doses of the drug to kill melanoma cells are major drawbacks for this purpose. Considering that melanoma is restricted to the skin at early stages, the topical application of IBR might constitute an effective and safer administration route. In this study, we determined IBR's toxicity and dermatokinetics using human primary cells and human organotypic skin explant cultures (hOSECs). Methods: After demonstrating that human primary fibroblasts and keratinocytes present IBR target genes, the cytotoxicity of the drug was determined using the MTT and annexin V/PI staining assays. IBR toxicity in the skin was assessed using the TTC assay, and the irritation potential was established using histological assessment. Finally, IBR cutaneous permeation was assessed ex vivo to determine the drug dermatokinetics. Results: Our findings reveal that IBR exerts dose-dependent toxicity towards skin cells, presenting an IC50 in the same range as melanoma cells. The topical application of the drug successfully reduced irritation and toxicity in the skin, and the drug was shown to successfully permeate the stratum corneum and reach the viable skin layers in therapeutic concentrations. Conclusions: Overall, our data encourage the topical application of IBR to treat melanoma, paving the way for future studies in this theme.